Comparative analysis of antioxidant and anti-inflammatory activities of red, blue, and black tea for health benefits - Patel, Sanjana; Dey, Rohit; Verma, Khushi; Deshbhratar, Radha; Maru, Kamal Kishore; Sharma, Porshia; Limaye, Rashmi; Puri, Payal (Brazilian Journal of Science, 2023)
The current COVID-19 predicament necessitates a greater emphasis on developing immunity. Herbal teas are abundant in antioxidants which are important for strengthening the immune system. Hot water decoction of Hibiscus rosa sinensis flowers (red tea), Clitoria ternatea flowers (blue tea) and commercially available black tea were evaluated by comparing for in vitro antioxidant and anti-inflammatory properties. Anthocyanin pigment in red, blue, and black tea demonstrated Rf values of 0.52, 0.86 and 0.78 respectively. Blue and black teas exhibited dominance of polyphenols, flavonoids, tannins, glycosides, terpenoids, saponins as compared to red tea. The highest total phenolic (12.25 ± 0.245 mg GAE/gm extract-1) and flavonoid (15.84 ± 0.268mg QE/gm extract-1) content were observed with black and blue tea respectively. Blue tea, and black tea extracts exhibited FRPA values of 1.81 ± 0.413 mg and 1.93 ± 0.178 mg AAE per gram extract-1 respectively. Black tea exhibits the highest antioxidant capacity in reducing molybdate ions (1.94 ± 0.354 mg AAE per gram extract-1) followed by blue tea (1.56 ± 0.199 mg AAE per gram extract-1). Blue tea extract at a very low concentration showed highest percentage hemolytic inhibition (57.14 ± 0.567%). According to the study, blue tea is a rich source of antioxidants with significant anti-inflammatory properties. The research may offer a valuable supplementary strategyfor its therapeutic applications.